Differential auxin transport and accumulation in the stem base lead to profuse adventitious root primordia formation in the aerial roots (aer) mutant of tomato (Solanum lycopersicum L.) - Mignolli, Francesco (2017)
Fil: Mignolli, Francesco. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.